Mosaico de áreas protegidas do Espinhaço: Alto Jequitinhonha - Serra do Cabral, Minas Gerais e os desafios para sua efetividade - Gabriel Carvalho de Ávila (2014)
One way to facilitate participatory management of land and make the integration of near, contiguous or overlapping Protected Areas (PAs) is through the institution of Mosaics. Several mosaics have already been created in our country. However, there is great disparity in the implementation level of these, result of several factors such as availability of financial resources, commitment and involvement of public agencies, NGOs and civil society in improving the proposal; adhesion and support of the staff of Protected Areas, among others. In 2010 was established the Espinhaço: Alto Jequitinhonha - Serra do Cabral Mosaic which has PAs of the three spheres of government control: Federal, State and Municipal . The Espinhaço Mosaic is in a very basic level of implantation and requires objective analysis in order to give subsidies to its implementation process, avoiding that thus this project to be abandoned. So, this study aimed to characterize the social and environmental setting of the region of Espinhaço mosaic; evaluate the effectiveness of the mosaic PAs management and identify the main threats to conservation; analyze the impact of the create of the Mosaic in the social participation and management of PAs, through the vision of their managers; and to identify the thematic lines and targets of preferential activities that enable the advance of the proposal. For this a quantitative-qualitative analysis was performed by relying on literature and documents. There was also applied a tool to measure the management effectiveness of PAs in the Mosaic (Tracking Tool) and a questionary with the managers of the PAs. This research produced a reference document with data about the territory of the Espinhaço Mosaic, with information of its PAs, its level of implementation, its needs and threats. It was identified, according to the managers impression, that in general, the mosaic has low impact in the management improving of PAs and in fostering social participation. It was concluded that to fulfill its role, the mosaic should seek for financial sustainability of its staff and also support the search for warranty and sufficiency of financial resources for the PAs involved. The Mosaic still needs to work subjects with greater reflex in the management of the PAs and facilitate of social participation. Therefore, it is desirable to have a major overhaul in the Mosaic strategic planning in order to meet the above issues, since they are not met by the current layout of its planning.